2011
DOI: 10.5194/angeo-29-1699-2011
|View full text |Cite
|
Sign up to set email alerts
|

Energy and flux variations across thin auroral arcs

Abstract: Two discrete auroral arc filaments, with widths of less than 1 km, have been analysed using multi-station, multi-monochromatic optical observations from small and medium field-of-view imagers and the EISCAT radar. The energy and flux of the precipitating electrons, volume emission rates and local electric fields in the ionosphere have been determined at high temporal (up to 30 Hz) and spatial (down to tens of metres) resolution. A new time-dependent inversion model is used to derive energy spectra from EISCAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 32 publications
6
47
0
Order By: Relevance
“…Lanchester et al [] demonstrated the strength of the method by determining the peak energy and flux of the precipitation forming a number of dynamic auroral events with widths of the order of 100 m perpendicular to the geomagnetic field. Dahlgren et al [] used the technique in an investigation of the role of sheared aurora at boundary regions. In the study, it was found that a thin, sheared auroral arc appeared on the boundary between two different precipitating electron populations of different energies, where an energy gradient and increased number flux were present.…”
Section: Novel Scientific Results From Askmentioning
confidence: 99%
“…Lanchester et al [] demonstrated the strength of the method by determining the peak energy and flux of the precipitation forming a number of dynamic auroral events with widths of the order of 100 m perpendicular to the geomagnetic field. Dahlgren et al [] used the technique in an investigation of the role of sheared aurora at boundary regions. In the study, it was found that a thin, sheared auroral arc appeared on the boundary between two different precipitating electron populations of different energies, where an energy gradient and increased number flux were present.…”
Section: Novel Scientific Results From Askmentioning
confidence: 99%
“…The appearance of optical aurora often suggests also the presence of small-scale, less than a kilometre wide FACs. These have indeed been found with the help of sufficiently rapidly sampling magnetometers on board satellites in low orbits -for example, see Dahlgren et al (2011). The Ørst-edt and CHAMP satellites, launched in 1999 and 2001, respectively, featured high-precision and fast sampling (10 and 50 Hz) fluxgate magnetometers as well as polar orbits.…”
Section: Introductionmentioning
confidence: 81%
“…), optical instruments are usually absolute calibrated by exposing the instrument to a calibration light source with a known spectral radiant sterance corresponding to a certain column emission rate (see, for example, Trondsen, 1998;Mäkinen, 2001;Brändström, 2003, and references therein). Instead of using calibration light sources, some instruments are calibrated by using known spectra of stars (for example Dahlgren et al, 2011).…”
Section: B U E Brändström Et Al: Intercalibration Results 2011mentioning
confidence: 99%